Stability and In vitro Comparative Study of Optimized Non-Aqueous Nano Emulsion of Naproxen with Marketed Formulations - Bhagat, Babasaheb Vasantrao (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The current study’s objective was to evaluate stability study and compare and analyze the improved nonaqueous nanoemulsion (NANE) of naproxen with marketed gel formulations (M1 and M2). Methods: Utilizing a low energy emulsification technique, an optimized NANE of naproxen was prepared. The comparison research was assessed for general appearance, pH, viscosity, drug content, and in vitro drug release against marketed formulations. Six months of stability investigations were carried out as per ICH Q1A R2 guideline. During stability study, phase separation, creaming, cracking, phase inversion, color, pH, viscosity, and drug content were evaluated. Results: In comparative study, pH of NANE and marketed formulations M1 and M2 was found to be 5.5 ± 0.36, 5.8 ± 0.80, and 5.6 ± 0.08, respectively. Viscosity is a crucial characteristic of NANE; it was found that optimized NANE showed lower viscosity (54.40 ± 1.25 mPa.S) than marketed formulations (M1- 78.20 ± 0.76 mPa.S, M2-80.56 ± 0.28 mPa.S). Drug content of NANE of naproxen and marketed formulations was found to be 95 ± 0.46, 98 ± 0.16, and 97 ± 0.38, respectively. From the in vitro drug release study, we found that optimized NANEs of naproxen showed highest percentage of drug release (96.24 ± 1.96) as compared to marketed formulation M1 (90.58 ± 1.31) and M2 (89.15 ± 1.33), respectively. No phase separation, creaming, cracking and phase inversion was seen after agitation, centrifugation, and freeze-thaw cycles. This demonstrated the NANE excellent stability in the presence of gravity. pH and drug content of NANE was stable within 6 months of stability study. Viscosity of optimized NANEs decreased from 55.80 ± 0.48 mPa.S to 51.20 ± 1.06 mPa.S within 6 months in accelerated stability study and stable in intermediate stability study. Conclusion: It was discovered following a stability assessment that there was no indication of instability.